2020
DOI: 10.1002/jev2.12042
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer extracellular vesicles mediate intercellular communication with bone marrow cells and promote metastasis in a cholesterol‐dependent manner

Abstract: Primary tumours can establish long‐range communication with distant organs to transform them into fertile soil for circulating tumour cells to implant and proliferate, a process called pre‐metastatic niche (PMN) formation. Tumour‐derived extracellular vesicles (EV) are potent mediators of PMN formation due to their diverse complement of pro‐malignant molecular cargo and their propensity to target specific cell types (Costa‐Silva et al., 2015; Hoshino et al., 2015; Peinado et al., 2012; Peinado et al., 2017).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 60 publications
(71 reference statements)
3
26
0
Order By: Relevance
“…As observed in this study, EVs from the acute megakaryoblastic leukemia cell line CHRF-288-11 were readily taken up by HSPCs in coculture, suggesting cancer cells can influence the expression of stem cells. Studies have reported on the effects of cancer cell derived EVs on stem cells (Chin & Wang, 2016; Daßler-Plenker, Küttner, & Egeblad, 2020; Henrich et al, 2020) and in this study we were able to observe the large extent of cancer-derived EVs uptake by HSPCs.…”
Section: Discussionsupporting
confidence: 57%
“…As observed in this study, EVs from the acute megakaryoblastic leukemia cell line CHRF-288-11 were readily taken up by HSPCs in coculture, suggesting cancer cells can influence the expression of stem cells. Studies have reported on the effects of cancer cell derived EVs on stem cells (Chin & Wang, 2016; Daßler-Plenker, Küttner, & Egeblad, 2020; Henrich et al, 2020) and in this study we were able to observe the large extent of cancer-derived EVs uptake by HSPCs.…”
Section: Discussionsupporting
confidence: 57%
“…The formation of PMN involves persistent long-range intercellular communication mediated by soluble or membrane-bound factors originating from the primary tumor [113,116]. These factors traverse through vascular and interstitial spaces and eventually engage with the cholesterolrich plasma membrane of recipient cells at pre-metastatic organ sites [117]. Tumor-derived exosomes remodel the ECM by accumulating fibronectin and promoting ECM-modifying enzyme lysyl oxidase (LOX) crosslinking to enhance the adhesion of the bone-marrowderived cells which are essential pre-metastatic niche components [113,118,119].…”
Section: Tumor-derived Exosome Mediated Communication In Pre-metastatmentioning
confidence: 99%
“…Tumor-derived exosomes remodel the ECM by accumulating fibronectin and promoting ECM-modifying enzyme lysyl oxidase (LOX) crosslinking to enhance the adhesion of the bone-marrowderived cells which are essential pre-metastatic niche components [113,118,119]. Interestingly, a recent study elegantly demonstrates that EV-mediated communication between PCa cells and bone marrow is mediated by cholesterol homeostasis in bone marrow myeloid cells [117]. They showed that PCa EV uptake by bone marrow myeloid cells in vitro and in vivo leads to activated NF-κB signaling, reduced myeloid thrombospondin-1 expression and enhanced osteoclast differentiation.…”
Section: Tumor-derived Exosome Mediated Communication In Pre-metastatmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein transfer of pyruvate kinase M2 from EVs to these recipient cells led to increased levels of the chemokine CXCL12 in a HIF-1α–dependent mechanism ( 77 ), which likely contributed to an inflammatory response ( 78 ) that prepared the premetastatic niche. Additionally, the introduction of EVs derived from the enzalutamide resistant PCa cell line CW-R1 resulted in NF-κB signaling and enhanced osteoclast differentiation in bone marrow stromal cells ( 79 ), which is an initial step in reprogramming the bone microenvironment to allow for tumor cell proliferation and metastasis ( 80 ).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%